Conspecific visual cues: the relative importance of interference and exploitation competition among tadpoles of Rana kukunoris. Issue 2 (4th March 2017) - Yu, T.L.; Lambert, M.R.
Abstract : Anuran larvae may use three types of cues (i.e. chemical, visual and tactile) in intraspecific competition, and subsequently mediate their growth and development; these cues are poorly understood and controversial. Here, we investigate the relative contribution of these cues in interference and exploitative mechanisms among Rana kukunoris tadpoles. In particular, we isolate the importance of visual interference signals against direct exploitation. Our results demonstrate that larvae reared alone and blinded to conspecifics had a longer larval period and grew larger than tadpoles reared alone but with conspecific visual cues or compared to tadpoles reared with conspecifics. Thus, we show evidence of visual interference competition, in which conspecific visual signals inhibit the growth of tadpoles and shorten larval development but do not reduce survival. We suggest tadpoles of R. kukunoris may use visual cues throughout ontogeny, delaying larval development to maximize individual fitness when environmental conditions (abundant food and space) allow for increased growth in the presence of few conspecifics.